FUNDING ANALYSIS OF MURABAHAH, MUSYARAKAH, AND MUDHARABAH ON RETURN ON ASSET ON SHARIA BANKS IN INDONESIA - Rihfenti Ernayani; Robiyanto Robiyanto (Jurnal Dinamika Ekonomi & Bisnis, 2019)
The purpose of this study to examine, analyze, and prove the effect of mudharabah financing, musyarakah financing and murabahah financing on return on assets of Sharia Commercial Banks in Indonesia. The sample is taken by purposive sampling; there are eight Sharia Commercial Banks registered at Bank Indonesia which become samples in this study. Regression analysis used to analyze the data. Mudharabah financing and murabahah financing doesn’t affect return on assets significantly, while musyarakah financing has a negative significant effect toward return on assets.